School operators' perspectives on the administrative performance of teachers and principals: Barriers, challenges, and recommendations for improving efficiency - Asep Yudianto; Nurul Hadi Pauji; Ridwan Eko Apriyanto; Imam Nururi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Administrative performance in schools plays a crucial role in ensuring effective management and educational quality. However, teachers and principals often face challenges related to workload and administrative complexity. This study aims to analyze the perspectives of school operators (OpS) on the administrative performance of teachers and principals, the obstacles encountered in administrative tasks, and their recommendations to overcome these challenges. Previous studies have shown that administrative burdens can affect teaching quality and leadership effectiveness, yet limited research has explored these issues from the perspective of school operators in Indonesia. Methods: This quantitative study employed a survey approach involving 493 respondents representing various educational levels across Indonesia. Data were collected using structured questionnaires and analyzed through descriptive and inferential statistical techniques to identify patterns, trends, and relationships among variables related to administrative performance. Findings: The majority of respondents came from Java Island, with a predominance of elementary school participants. Teachers’ administrative performance was generally rated as good, although they encountered obstacles such as heavy workloads, insufficient facilities, and frequent policy changes. Principals also demonstrated good administrative performance, particularly in communication and staff coordination, yet faced challenges related to limited time and coordination barriers. School operators recommended training in administrative technology, time management, and administrative leadership for improvement. Conclusion: The study concludes that continuous training, improved facilities, and consistent administrative policies are essential to enhance the efficiency and effectiveness of school administrative performance. Novelty/Originality of this article: This study contributes new insights by presenting the unique perspectives of school operators regarding the administrative performance of teachers and principals in Indonesia, emphasizing the need for policy and management reforms to support more efficient school administration.